Analisis Kejahatan Terorisme Berkedok Agama - Agus Handoko (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
Abstract:The term Terrorism surfaced in various parts of the world, both in European countries, the Middle East and even Asia, including Indonesia. Due to the emergence of every violence and destruction in every place with the loss of not only property and even human lives. The nickname of the Terrorists has always been addressed to certain groups who echoed jihad, and the events of terrorism which were of concern to the world at the time of the occurrence of an event the United States WTC (World Trade Center) Tower was bombed and destroyed on 11 September 2001. From the tragedy that eliminated thousands of human lives, the war on global terrorism (global war on terrorism) was officially proclaimed by Western countries. So that the study of terrorism invites the attention of various groups, both academics and agencies or national and international institutions by examining various aspects, namely through aspects of theology, ideology, and movements and networks. Until now terrorism has become a threat to the security and security of the country and also frightened the public. This paper will examine the growth of terrorism both inside and outside Indonesia which will elaborate terrorism in the name of religion.Keywords: Terrorism, Religious, Crime Abstrak.Istilah Terorisme mengemuka di berbagai belahan dunia, baik di negara-negara Eropa, Timur Tengah bahkan Asia termasuk Indonesia. Dikarenakan munculnya setiap kekerasan maupun kehancuran di setiap tempat dengan adanya kerugian tidak saja harta benda bahkan nyawa manusia. Julukan Teroris selalu dialamatkan pada kelompok tertentu yang mengumandangkan jihad, dan peristiwa terorisme yang menjadi perhatian dunia pada saat terjadinya suatu peristiwa Menara Kembar WTC (World Trade Center) milik Amerika Serikat dibom dan hancur pada tanggal 11 September 2001 lalu. Dari tragedi yang menghilangkan ribuan nyawa manusia, perang melawan terorisme global (global war on terrorism) resmi dikumandangkan oleh negara-negara Barat. Sehingga kajian mengenai terorisme mengundang perhatian berbagai kalangan, baik akademisi maupun instansi atau lembaga nasional maupun internasional dengan mengkaji dari berbagai macam aspek, yaitu melalui aspek Teologi, Ideologi, maupun gerakan-gerakan dan jaringannya. Sampai saat ini terorisme menjadi ancaman terhadap ketahanan dan keamanan negara dan juga membuat ketakutan di kalangan masyarakat. Makalah ini akan mengkaji seputar tumbuhnya terorisme baik di luar maupun dalam negeri Indonesia yang akan mengelaborasi terorisme atas nama keagamaan.Kata Kunci: Terorisme, Keagamaan, Kejahatan